2007
DOI: 10.1007/s10719-007-9086-4
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and serum α2-3- and α2-6-linkage specific sialylation changes in oral carcinogenesis

Abstract: Increased sialylation of cell surface glycoconjugates is among the key molecular changes associated with malignant transformation and cancer progression. We investigated significance of linkage-specific sialylation changes in oral carcinogenesis. Tissue and serum levels of total sialic acid (TSA), linkage-specific sialyltransferases (ST) and sialoproteins were analyzed from patients with oral precancerous conditions (OPC) and oral cancer as well as the post-treatment follow-up blood samples of oral cancer pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 42 publications
2
57
1
Order By: Relevance
“…13,27 Alterations in enzyme activity of a-2,3 and a-2,6 STs, and FUT have been reported in serum of oral cancer patients. 7,8 However, there are no earlier reports on mRNA levels of ST and FUT in oral cancer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…13,27 Alterations in enzyme activity of a-2,3 and a-2,6 STs, and FUT have been reported in serum of oral cancer patients. 7,8 However, there are no earlier reports on mRNA levels of ST and FUT in oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Previous studies from our laboratory have indicated elevated serum and tissue ST and FUT enzyme activities in oral cancer patients. 7,8 Elevations in serum and salivary sialic acid have been reported in oral cancer, which might be because of increase in ST or sialidase activities. 9 Various STs (ST3GAL, ST6GAL, ST6GALNAC, and ST8) are named according to the sialyl linkages they form.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,16,[25][26][27][28] In humans, metastasizing tumors are characterized by an increased expression of Sia-a2,6, whereas benign tumors express mainly Sia-a2,3. Moreover, a higher activity of ST-a2,6 has been reported in malignant colorectal cells 5,9,35 and oral cancers 30 as well as in serum of patients with metastasizing tumors.…”
mentioning
confidence: 94%